THE EFFECT OF MARKETING COMMUNICATION, EXPERIENTIAL MARKETING, AND CUSTOMER TRUST ON PURCHASE DECISIONS AT FORME FURNITURE - Budiyanto, Albert (ESENSI: Jurnal Manajemen Bisnis, 2025)
This study investigates whether marketing communication, experiential marketing, and customer trust jointly and individually have significant effects on purchase decisions at Forme Furniture. The research employs an associative (explanatory) design. The population comprises all Forme Furniture customers in 2023 (N = 107). Using non- probability, saturated (census) sampling, the sample equals the population (n = 107). Data analysis includes validity and reliability tests, multiple linear regression, and F- and t- tests. The F-test results indicate that marketing communication, experiential marketing, and customer trust collectively exert a significant effect on purchase decisions. The t-tests show that each predictor—marketing communication, experiential marketing, and customer trust has a positive, statistically significant partial effect on purchase decisions at Forme Furniture.